Complete Mapping of DNA‐Protein Interactions at the Single‐Molecule Level (Adv. Sci. 23/2021). Issue 23 (8th December 2021) - Liu, Wenzhe; Li, Jie; Xu, Yongping; Yin, Dongbao; Zhu, Xin; Fu, Huanyan; Su, Xiaodong; Guo, Xuefeng
Abstract : Single‐Molecule Studies An unprecedented high‐resolution single‐molecule electrical detection platform offering a complete description of protein‐DNA interactions is developed in article number 2101383 by Xiaodong Su, Xuefeng Guo, and co‐workers. Detailed investigation in real time shed light on the whole protein searching process with single‐base resolution. By in‐situ monitoring the trajectories of individual molecules, this single‐molecule platform unveils fundamental laws of protein‐DNA interactions, demonstrating infinite possibilities for the development of new chemistry and biophysics.